Compression index of soil - Poh, Kai Li. (2010)
The construction of foundations or other load-bearing structures causes the soil layers to compress due to an increase in the stress acting on the soil. This compression of the soil layers is caused by the deformation of soil structures or the reduction of void volume due to expulsion of water and air from the void spaces.